Enhancing patient-reported outcomes in stroke care: a path to improved well-being - Katzan, Irene L.; Thompson, Nicolas R.; Uchino, Ken; Lapin, Brittany (Frontiers in Neurology, 2025)
Patient-reported outcomes (PROs) present a valuable opportunity to enhance stroke care by capturing symptoms and experiences often missed by traditional outcome measures like the modified Rankin Scale. Despite similar clinician-reported scores, stroke survivors frequently experience varied symptoms across physical, emotional, and social domains that significantly impact their well-being. This commentary examines the evolving role of PROs in stroke care, highlighting their potential to guide personalized treatment strategies. We present cases demonstrating how PROs reveal meaningful clinical differences among seemingly similar patients and discuss implementation challenges in clinical practice. While barriers exist, including time constraints and the complexity of post-stroke symptoms, solutions such as specialized recovery clinics and digital health programs could help bridge the gap between identifying patient needs and delivering targeted interventions. As stroke care evolves, incorporating PROs may unlock new opportunities for improving outcomes by addressing the comprehensive needs of stroke survivors throughout their recovery journey.